Rancang Bangun Aplikasi Walking Log dalam Penghitungan Jumlah Langkah untuk Pembakaran Kalori Tubuh - Raharja, Wahyu Kusuma; Azhari, M. Fajar; Alfitra, Zidan (Universitas Gunadarma, 2025)
Walking is a light physical activity that has a positive impact on health. A pedometer can be used to count the number of steps taken while walking. However, these devices usually have limited features and seem impractical to use. Current mobile technology developments, especially smartphones, can be used as an alternative to using a pedometer. The Walking Log application was created as an application to count the number of steps walked and the body's calorie burn. This application was created through several stages including planning, design, coding, and testing. In the planning stage, information will be collected regarding the number of steps, calorie burn, the sensors used, and the process of creating an Android application. At the design stage, a navigation structure, display design and file structure for storing historical data will be created.. In the coding stage, the application will be created using Android Studio. This research produced an Android application file named walking-log.apk with a size of 3,023 kilobytes. The walking log application consists of six menus: the main screen, track menu, settings menu, history menu, and about menu. Based on the results of the trial process, the application can run well on several devices that have met the minimum requirements to be able to run this application, namely Android smartphones with a minimum Android operating system. In the accuracy and error percentage tests, this application has an error percentage of ±2.12%. This error value shows that the application that has been built has good accuracy